The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/diagnostics11112145
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Nipple Areola Complex Sensation with Semmes-Weinstein Monofilaments—Normative Values and Its Covariates

Abstract: Objective: To establish normative data for nipple-areola complex (NAC) sensibility examined with Semmes-Weinstein monofilament test (SWMT) and two-point discrimination (TPD) in women with varying breast sizes, including women with gigantomastia. We also aimed to identify clinical variables influencing NAC sensation. Methods: A total of 320 breasts in 160 Caucasian women (mean age 33.6 years, SD 11 years) were examined (including 50 hypertrophic breasts). NACs sensation was examined using Semmes-Weinstein monof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Higher age, larger breasts, previous pregnancies and breastfeeding, and higher body mass index (BMI) negatively influence breast sensation. Contrary to common assumptions, the NAC appears less sensitive than surrounding breast skin ( 31 , 32 ).…”
Section: Resultscontrasting
confidence: 65%
“…Higher age, larger breasts, previous pregnancies and breastfeeding, and higher body mass index (BMI) negatively influence breast sensation. Contrary to common assumptions, the NAC appears less sensitive than surrounding breast skin ( 31 , 32 ).…”
Section: Resultscontrasting
confidence: 65%
“…All these methods have been developed to improve the variables which add to the "perfect breast" such as: breast shape, footprint, and nipple-areolar complex (NAC) sensation and projection for both better aesthetic and functional results. [4][5][6][7][8][9][11][12][13][14]. Furthermore, it seems to be important to verify the available surgical techniques in the aspect of the possibility to achieve "clinically" symmetric breasts.…”
Section: Introductionmentioning
confidence: 99%
“…These values seem high for a nonoperated, healthy breast, especially when comparing them to other studies measuring sensation in the healthy breast. Bijkerk et al 8 used the 20-piece kit of the Semmes-Weinstein monofilaments to measure breast sensation and found values ranging from 2.36 to 3.22, translating to pressures between 0.02 and 0.16 g. Tairych et al 9 used the same monofilaments to analyze breast sensation in women with various breast sizes, and Kasielska-Trojan et al 10 specifically evaluated the nipple-areolar complex. All these studies found comparable results regarding the nonoperated breast.…”
mentioning
confidence: 99%